Independent Effects of Eye and Hand Movements on Visual Working Memory - Hanning, Nina M.; Deubel, Heiner (Frontiers in Systems Neuroscience, 2018)
Both eye and hand movements have been shown to selectively interfere with visual working memory. We investigated working memory in the context of combined eye-hand movements to approach the question whether the eye and the hand movement systems independently interact with visual working memory. Participants memorized several locations and performed eye, hand, or combined eye-hand movements during the maintenance interval. Subsequently, we tested spatial working memory at the eye or the hand motor goal, and at action-irrelevant locations. We found that for single eye and single hand movements, memory at the eye or hand target was significantly improved compared to action-irrelevant locations. Remarkably, when an eye and a hand movement were prepared in parallel, but to distinct locations, memory at both motor targets was enhanced – with no tradeoff between the two action goals. This suggests that eye and hand movements independently enhance visual working memory at their goal locations, resulting in an overall working memory performance that is higher than that expected when recruiting only one effector.